All-solid-state electrolyte membrane and preparation method thereof
By adopting a multi-dimensional particle size-matched low-pore structure and a polymer solid electrolyte coating sulfide solid electrolyte in an all-solid-state electrolyte membrane, the impedance and energy density problems caused by insufficient or excessive thickness of the electrolyte membrane are solved, achieving Higher film strength and battery performance.
Patent Information
- Application Number
- CN202411402951.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-24
AI Technical Summary
In industrial applications, existing all-solid electrolyte membranes have problems such as insufficient strength when the thickness is too thin, increased battery impedance and reduced energy density when the thickness is too large, high impedance caused by solid-solid contact, and moisture sensitivity of sulfide electrolytes.
The solid electrolyte prefabricated layer with a low pore structure with multi -dimensional particle size matching includes a polymer solid electrolyte, sulfide solid electrolyte, and adhesive. High membrane strength.
It improves the strength and pore rate of solid electrolyte, reduce the resistance and sensitivity of the battery, enhance the compatibility of the electrolyte film and positive/negative chips, and improve the overall performance of the battery.
Smart Images

Figure CN119361814A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, in particular to an all-solid electrolyte membrane and a preparation method thereof. Background Art
[0002] Lithium / sodium ion batteries have the advantages of high energy density, long cycle life, and no memory effect. However, current liquid lithium / sodium batteries have disadvantages such as poor thermal stability, flammability, and narrow electrochemical window.
[0003] In order to comprehensively improve the key performance of lithium / sodium secondary batteries, such as energy density, safety, and stability, the use of all-solid-state electrolytes can meet the battery's high energy density, high safety, and high stability requirements. In all-solid-state batteries, the solid electrolyte membrane is the most important component.
[0004] After searching patent number CN117673442A, the preparation method of oxide solid electrolyte membrane includes mixing a high molecular polymer with a first solvent and homogenizing to obtain agent A; nano-micronizing oxide powder, dispersant and second solvent, and defining the oxide slurry after nano-micronizing as agent B; taking a certain amount of agent B, adding a certain amount of protective agent to the agent B, and then homogenizing, and defining the slurry obtained after homogenization as agent C; taking a certain amount of agent A and a certain amount of agent C, mixing and homogenizing; taking a certain amount of agent B, adding it to the mixed slurry of agent A and agent C for homogenization, lithium fluorination reaction occurs, and solid electrolyte slurry is formed; and producing the oxide solid electrolyte membrane by coating. The preparation method of the present invention has simple process, few side reactions, and the prepared oxide solid electrolyte membrane has uniform thickness, good surface flatness and good conductivity.
[0005] However, at the current stage, the solid electrolyte membranes of the above patents still have many technical difficulties to be solved in industrial applications, such as: when the electrolyte membrane is thin, its strength is low, which is not conducive to industrial production; when the electrolyte membrane is thick, the battery impedance increases and the energy density of the battery is reduced; high impedance caused by solid-solid contact of the electrolyte; sulfide electrolytes are sensitive to moisture, and other issues. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides an all-solid-state electrolyte membrane and a method for preparing the same, which solves the problems that when the electrolyte membrane is thin, its strength is low, which is not conducive to industrial production; when the electrolyte membrane is thick, the battery impedance increases and the energy density of the battery is reduced; the high impedance is caused by solid-solid contact of the electrolyte; and the sulfide electrolyte is sensitive to moisture.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: an all-solid-state electrolyte membrane, comprising a base membrane and a solid electrolyte prefabricated layer arranged on the surface of the base membrane, the solid electrolyte prefabricated layer is arranged as a low-porosity structure with multi-dimensional particle size matching, the solid electrolyte prefabricated layer comprises a polymer solid electrolyte, a sulfide solid electrolyte and an adhesive, and the sulfide solid electrolyte is uniformly coated with the polymer solid electrolyte.
[0008] Preferably, the base film material is one of polyimide film, polyetherimide film, polytetrafluoroethylene film, cellulose film, polyester film, and polyacrylonitrile-based composite film.
[0009] Preferably, the base film has a thickness of 3 to 15 um.
[0010] Preferably, the porosity of the base film is 50% to 90%.
[0011] Preferably, the base film has a tensile strength of 50 to 200 MPa.
[0012] Preferably, the solid electrolyte membrane has a thickness of 5 to 15 um.
[0013] Preferably, the polymer solid electrolyte is at least one or more of polyethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, and hydrogenated nitrile rubber.
[0014] Preferably, the sulfide solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one or more of.
[0015] Preferably, the solid electrolyte membrane has a thickness of 5 to 30 μm.
[0016] The present invention provides a method for preparing an all-solid electrolyte membrane, comprising the following steps:
[0017] The first step is to prepare the first type of composite solid electrolyte particles M11:
[0018] Adding a polymer solid electrolyte P into a high-temperature vacuum mixer and fully melting it under certain temperature and stirring conditions; adding a first type of sulfide electrolyte S1 and fully mixing it under certain temperature and stirring conditions to form a molten slurry M10; using a spray device to spray M10 into first type composite solid electrolyte particles M11;
[0019] Preferably, the particle size distribution of the first type of sulfide electrolyte S1 is: Dmax (<2.0um), D50 (1.0-1.2um);
[0020] Preferably, the weight ratio of the polymer solid electrolyte P to the first type sulfide electrolyte S1 is (15:85) to (35:65);
[0021] Preferably, the first type of composite solid electrolyte particles M11 are polymer solid electrolyte particles or sulfide solid electrolyte particles coated with polymer solid electrolyte, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10 to 50 nm;
[0022] Preferably, the particle size distribution of the first type of composite solid electrolyte particles M11 is: Dmax (<2.5um), D50 (1.5-1.9um);
[0023] The second step is to prepare the second type of composite solid electrolyte particles M21:
[0024] Adding a polymer solid electrolyte P into a high-temperature vacuum mixer and fully melting it under certain temperature and stirring conditions; adding a second type of sulfide electrolyte S2 and fully mixing it under certain temperature and stirring conditions to form a molten slurry M20; using a spray device to spray M20 into first type composite solid electrolyte particles M21;
[0025] Preferably, the particle size distribution of the second type of sulfide electrolyte S2 is: Dmax (<1.0um), D50 (0.6-0.75um);
[0026] Preferably, the weight ratio of the polymer solid electrolyte P to the second type sulfide electrolyte S2 is (30:70) to (45:55);
[0027] Preferably, the second type of composite solid electrolyte particles M21 are polymer solid electrolyte particles or sulfide solid electrolyte particles coated with polymer solid electrolyte, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 40 to 80 nm;
[0028] Preferably, the particle size distribution of the second type of composite solid electrolyte particles M21 is: Dmax (<1.7um), D50 (0.8-1.0um);
[0029] The third step is the preparation of the solid electrolyte prefabricated membrane F1:
[0030] M11, M21 and adhesive are mixed evenly according to a certain ratio, and then the adhesive is fiberized and granulated so that the adhesive fibers fully contact and cover the M11 and M21 particles; the M11 and M21 particles covered with the adhesive fibers are pressed into a solid electrolyte prefabricated membrane F1 by a membrane forming device;
[0031] Preferably, the adhesive comprises PVDF or PTFE.
[0032] Preferably, the solid electrolyte prefabricated membrane F1 has a thickness of 2 to 10 um.
[0033] Preferably, the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is (65:25:10) to (50:35:15).
[0034] The fourth step is the preparation of all-solid electrolyte membrane FF:
[0035] Using hot pressing equipment to press the base film F0 and the solid electrolyte prefabricated film F1 into a solid electrolyte film FF under certain temperature and pressure conditions;
[0036] Preferably, the temperature is 45°C to 90°C.
[0037] Preferably, the pressure is 5 to 20 MPa.
[0038] The present invention also provides an all-solid-state battery, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane spaced between the positive electrode sheet and the negative electrode sheet.
[0039] The present invention provides an all-solid electrolyte membrane and a preparation method thereof. Compared with the prior art, it has the following beneficial effects:
[0040] 1. The all-solid-state electrolyte membrane and its preparation method provide higher membrane strength through the base membrane, so that the solid electrolyte membrane can be made thinner. The introduction of elastic polymer solid electrolyte coated on the surface of the sulfide solid electrolyte can make the contact between the solid electrolyte particles better, and the obtained solid electrolyte membrane has better compatibility with the positive / negative electrode sheets, thereby effectively reducing the high impedance problem caused by solid-solid contact in conventional all-solid-state batteries.
[0041] 2. The all-solid-state electrolyte membrane and its preparation method can also improve the high water sensitivity of the sulfide solid electrolyte by coating the surface of the sulfide solid electrolyte with a polymer solid electrolyte, so that the high ionic conductivity of the sulfide solid electrolyte can play a more stable role, and the polymer solid electrolyte also has certain ionic conductivity, which can further reduce the high impedance problem of the all-solid-state battery as a whole.
[0042] 3. The all-solid-state electrolyte membrane and its preparation method use solid electrolyte particles with different particle size distributions to match each other, and the resulting solid electrolyte membrane has lower pores to achieve better ion transport performance, reduce interface resistance, and improve the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 It is a schematic diagram of the structure of the all-solid-state electrolyte membrane of the present invention. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Please refer to the attached Figure 1
[0046] Embodiment 1:
[0047] A solid electrolyte membrane for an all-solid-state battery, comprising a base membrane and a solid electrolyte prefabricated layer arranged on the surface of the base membrane, wherein the solid electrolyte prefabricated layer is arranged as a low-porosity structure with multi-dimensional particle size matching, the solid electrolyte prefabricated layer comprises a polymer solid electrolyte, a sulfide solid electrolyte and an adhesive, and the sulfide solid electrolyte is uniformly coated by the polymer solid electrolyte, the base membrane material is one of a polyimide membrane, a polyetherimide membrane, a polytetrafluoroethylene membrane, a cellulose membrane, a polyester membrane, and a polyacrylonitrile-based composite membrane, and the polymer solid electrolyte is a polyimide membrane. At least one or more of ethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, and hydrogenated nitrile rubber, wherein the sulfide solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one or more of.
[0048] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is PEO, the sulfide solid electrolyte is Li2S-P2S5-LiCl, and the adhesive is PTFE.
[0049] The preparation method of the solid electrolyte membrane is as follows:
[0050] 1) Add polymer solid electrolyte P to a high-temperature vacuum mixer, heat to 75°C ± 5°C, stir for 30 minutes until completely melted, add the first type sulfide electrolyte S1, mix for 30 minutes, maintain the temperature at 75°C ± 5°C, rotate at a stirring speed of 20 Hz, and rotate at a dispersion speed of 3000 rpm to fully mix into a molten slurry M10, and use a spray device to spray M10 into first type composite solid electrolyte particles M11, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10 to 50 nm;
[0051] The particle size distribution of the first type sulfide electrolyte S1 is: Dmax (<2.0um), D50 (1.0~1.2um), the weight ratio of the polymer solid electrolyte P and the first type sulfide electrolyte S1 is 20:80, the first type composite solid electrolyte particle M11 is a polymer solid electrolyte particle or a sulfide solid electrolyte with a polymer solid electrolyte coated on the surface, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10~50nm, and the particle size distribution of the first type composite solid electrolyte particle M11 is: Dmax (<2.5um), D50 (1.5~1.9um).
[0052] 2) Add polymer solid electrolyte P to a high-temperature vacuum mixer and mix for 90 minutes, maintain the temperature at 160°C ± 5°C, rotate at a stirring speed of 30 Hz, and rotate at a dispersion speed of 3500 rpm to fully melt it, add the second type of sulfide electrolyte S2, and fully mix it under certain temperature and stirring conditions to form a molten slurry M20; use a spray device to spray M20 into the first type of composite solid electrolyte particles M21;
[0053] The particle size distribution of the second type sulfide electrolyte S2 is: Dmax (<1.0um), D50 (0.6-0.75um), the weight ratio of the polymer solid electrolyte P and the second type sulfide electrolyte S2 is 35:65, the second type composite solid electrolyte particles M21 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 40-80nm, and the particle size distribution of the second type composite solid electrolyte particles M21 is: Dmax (<1.7um), D50 (0.8-1.0um);
[0054] 3) M11, M21 and a binder are mixed uniformly according to a certain ratio, and then the binder is fiberized and granulated so that the binder fibers fully contact and cover the M11 and M21 particles, and the M11 and M21 particles covered with the binder fibers are pressed into a solid electrolyte prefabricated membrane F1 by a membrane forming device,
[0055] The thickness of the solid electrolyte prefabricated membrane F1 is 2-10 um, and the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is 60:30:10.
[0056] 4) Using hot pressing equipment at a preheating temperature of 60°C ± 5°C, a rolling pressure of 10-15 MPa, and a rolling speed of 70-90 m / min, the base film F0 and the solid electrolyte prefabricated film F1 are pressed into a solid electrolyte membrane FF.
[0057] The all-solid electrolyte membrane and positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery, and this assembly is a conventional all-solid-state battery assembly method.
[0058] Embodiment 2:
[0059] A solid electrolyte membrane for an all-solid-state battery, comprising a base membrane and a solid electrolyte prefabricated layer arranged on the surface of the base membrane, wherein the solid electrolyte prefabricated layer is arranged as a low-porosity structure with multi-dimensional particle size matching, the solid electrolyte prefabricated layer comprises a polymer solid electrolyte, a sulfide solid electrolyte and an adhesive, and the sulfide solid electrolyte is uniformly coated by the polymer solid electrolyte, the base membrane material is one of a polyimide membrane, a polyetherimide membrane, a polytetrafluoroethylene membrane, a cellulose membrane, a polyester membrane, and a polyacrylonitrile-based composite membrane, and the polymer solid electrolyte is a polyimide membrane. At least one or more of ethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, and hydrogenated nitrile rubber, wherein the sulfide solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one or more of.
[0060] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is PVDF-HFP, the sulfide solid electrolyte is Li2S-P2S5-LiCl, and the adhesive is PTFE.
[0061] The preparation method of the solid electrolyte membrane is the same as that of Example 1, wherein the particle size distribution of the first type sulfide electrolyte S1 is: Dmax (<2.0um), D50 (1.0-1.2um), the weight ratio of the polymer solid electrolyte P and the first type sulfide electrolyte S1 is 20:80, the first type composite solid electrolyte particles M11 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes on the surface, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10-50nm, and the particle size distribution of the first type composite solid electrolyte particles M11 is: Dmax (<2.5um), D50 (1.5-1.9um);
[0062] The particle size distribution of the second type sulfide electrolyte S2 is: Dmax (<1.0um), D50 (0.6-0.75um), the weight ratio of the polymer solid electrolyte P and the second type sulfide electrolyte S2 is 35:65, the second type composite solid electrolyte particles M21 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 40-80nm, and the particle size distribution of the second type composite solid electrolyte particles M21 is: Dmax (<1.7um), D50 (0.8-1.0um);
[0063] The thickness of the solid electrolyte prefabricated membrane F1 is 2-10 um, and the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is 60:30:10.
[0064] The all-solid electrolyte membrane and positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery, and this assembly is a conventional all-solid-state battery assembly method.
[0065] Different from Example 1, the solid electrolyte membrane of this embodiment selects PVDF-HFP, i.e., polyvinylidene fluoride-hexafluoropropylene copolymer, for the polymer solid electrolyte. During the preparation process, the melting temperature of the polymer solid electrolyte is 180°C±5°C, and the reaction temperature when adding sulfide solid electrolyte and adhesive is also controlled to be 180°C±5°C.
[0066] Embodiment 3:
[0067] A solid electrolyte membrane for an all-solid-state battery, comprising a base membrane and a solid electrolyte prefabricated layer arranged on the surface of the base membrane, wherein the solid electrolyte prefabricated layer is arranged as a low-porosity structure with multi-dimensional particle size matching, the solid electrolyte prefabricated layer comprises a polymer solid electrolyte, a sulfide solid electrolyte and an adhesive, and the sulfide solid electrolyte is uniformly coated by the polymer solid electrolyte, the base membrane material is one of a polyimide membrane, a polyetherimide membrane, a polytetrafluoroethylene membrane, a cellulose membrane, a polyester membrane, and a polyacrylonitrile-based composite membrane, and the polymer solid electrolyte is a polyimide membrane. At least one or more of ethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, and hydrogenated nitrile rubber, wherein the sulfide solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one or more of.
[0068] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is HNBR, the sulfide solid electrolyte is Li2S-P2S5-LiCl, and the adhesive is PTFE.
[0069] The preparation method of the solid electrolyte membrane is the same as that of Example 1, wherein the particle size distribution of the first type sulfide electrolyte S1 is: Dmax (<2.0um), D50 (1.0-1.2um), the weight ratio of the polymer solid electrolyte P and the first type sulfide electrolyte S1 is 20:80, the first type composite solid electrolyte particles M11 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes on the surface, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10-50nm, and the particle size distribution of the first type composite solid electrolyte particles M11 is: Dmax (<2.5um), D50 (1.5-1.9um);
[0070] The particle size distribution of the second type sulfide electrolyte S2 is: Dmax (<1.0um), D50 (0.6-0.75um), the weight ratio of the polymer solid electrolyte P and the second type sulfide electrolyte S2 is 35:65, the second type composite solid electrolyte particles M21 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 40-80nm, and the particle size distribution of the second type composite solid electrolyte particles M21 is: Dmax (<1.7um), D50 (0.8-1.0um);
[0071] The thickness of the solid electrolyte prefabricated membrane F1 is 2-10 um, and the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is 60:30:10.
[0072] The all-solid electrolyte membrane and positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery, and this assembly is a conventional all-solid-state battery assembly method.
[0073] Different from Example 1, the solid electrolyte membrane of this embodiment selects HNBR as the polymer solid electrolyte, the melting temperature of the polymer solid electrolyte during the preparation process is 160℃±5℃, and the reaction temperature when adding sulfide solid electrolyte and adhesive is also controlled to be 160℃±5℃.
[0074] Embodiment 4:
[0075] A solid electrolyte membrane for an all-solid-state battery, comprising a base membrane and a solid electrolyte prefabricated layer arranged on the surface of the base membrane, wherein the solid electrolyte prefabricated layer is arranged as a low-porosity structure with multi-dimensional particle size matching, the solid electrolyte prefabricated layer comprises a polymer solid electrolyte, a sulfide solid electrolyte and an adhesive, and the sulfide solid electrolyte is uniformly coated by the polymer solid electrolyte, the base membrane material is one of a polyimide membrane, a polyetherimide membrane, a polytetrafluoroethylene membrane, a cellulose membrane, a polyester membrane, and a polyacrylonitrile-based composite membrane, and the polymer solid electrolyte is a polyimide membrane. At least one or more of ethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, and hydrogenated nitrile rubber, wherein the sulfide solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one or more of.
[0076] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is a mixture of HNBR and PMMA, and the sulfide solid electrolyte Li2S-P2S5-LiCl adhesive is PTFE.
[0077] The preparation method of the solid electrolyte membrane is the same as that of Example 1, wherein the particle size distribution of the first type sulfide electrolyte S1 is: Dmax (<2.0um), D50 (1.0-1.2um), the weight ratio of the polymer solid electrolyte P and the first type sulfide electrolyte S1 is 20:80, the first type composite solid electrolyte particles M11 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes on the surface, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10-50nm, and the particle size distribution of the first type composite solid electrolyte particles M11 is: Dmax (<2.5um), D50 (1.5-1.9um);
[0078] The particle size distribution of the second type sulfide electrolyte S2 is: Dmax (<1.0um), D50 (0.6-0.75um), the weight ratio of the polymer solid electrolyte P and the second type sulfide electrolyte S2 is 35:65, the second type composite solid electrolyte particles M21 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 40-80nm, and the particle size distribution of the second type composite solid electrolyte particles M21 is: Dmax (<1.7um), D50 (0.8-1.0um);
[0079] The thickness of the solid electrolyte prefabricated membrane F1 is 2-10 um, and the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is 60:30:10.
[0080] The all-solid electrolyte membrane and positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery, and this assembly is a conventional all-solid-state battery assembly method.
[0081] Different from Example 1, the solid electrolyte membrane of this embodiment selects a mixture of HNBR and PMMA as the polymer solid electrolyte, and the melting temperature of the polymer solid electrolyte during the preparation process is 160°C±5°C. The reaction temperature when adding the sulfide solid electrolyte and the adhesive is also controlled to be 160°C±5°C.
[0082] Embodiment 5:
[0083] A solid electrolyte membrane for an all-solid-state battery, comprising a base membrane and a solid electrolyte prefabricated layer arranged on the surface of the base membrane, wherein the solid electrolyte prefabricated layer is arranged as a low-porosity structure with multi-dimensional particle size matching, the solid electrolyte prefabricated layer comprises a polymer solid electrolyte, a sulfide solid electrolyte and an adhesive, and the sulfide solid electrolyte is uniformly coated by the polymer solid electrolyte, the base membrane material is one of a polyimide membrane, a polyetherimide membrane, a polytetrafluoroethylene membrane, a cellulose membrane, a polyester membrane, and a polyacrylonitrile-based composite membrane, and the polymer solid electrolyte is a polyimide membrane. At least one or more of ethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, and hydrogenated nitrile rubber, wherein the sulfide solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one or more of.
[0084] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is PEO, the sulfide solid electrolyte is Li2S-GeS2-Sb2S5, and the adhesive is PTFE.
[0085] The preparation method of the solid electrolyte membrane is the same as that of Example 1.
[0086] The particle size distribution of the first type sulfide electrolyte S1 is: Dmax (<2.0um), D50 (1.0-1.2um), the weight ratio of the polymer solid electrolyte P and the first type sulfide electrolyte S1 is 20:80, the first type composite solid electrolyte particles M11 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes on the surface, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10-50nm, and the particle size distribution of the first type composite solid electrolyte particles M11 is: Dmax (<2.5um), D50 (1.5-1.9um);
[0087] The particle size distribution of the second type sulfide electrolyte S2 is: Dmax (<1.0um), D50 (0.6-0.75um), the weight ratio of the polymer solid electrolyte P and the second type sulfide electrolyte S2 is 35:65, the second type composite solid electrolyte particles M21 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 40-80nm, and the particle size distribution of the second type composite solid electrolyte particles M21 is: Dmax (<1.7um), D50 (0.8-1.0um);
[0088] The thickness of the solid electrolyte prefabricated membrane F1 is 2-10 um, and the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is 60:30:10.
[0089] The all-solid electrolyte membrane and positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery, and this assembly is a conventional all-solid-state battery assembly method.
[0090] Different from Example 1, the sulfide solid electrolyte in the solid electrolyte membrane of this embodiment is Li2S-GeS2-Sb2S5.
[0091] Embodiment 6:
[0092] A solid electrolyte membrane for an all-solid-state battery, comprising a base membrane and a solid electrolyte prefabricated layer arranged on the surface of the base membrane, wherein the solid electrolyte prefabricated layer is arranged as a low-porosity structure with multi-dimensional particle size matching, the solid electrolyte prefabricated layer comprises a polymer solid electrolyte, a sulfide solid electrolyte and an adhesive, and the sulfide solid electrolyte is uniformly coated by the polymer solid electrolyte, the base membrane material is one of a polyimide membrane, a polyetherimide membrane, a polytetrafluoroethylene membrane, a cellulose membrane, a polyester membrane, and a polyacrylonitrile-based composite membrane, and the polymer solid electrolyte is a polyimide membrane. At least one or more of ethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, and hydrogenated nitrile rubber, wherein the sulfide solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one or more of.
[0093] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is PEO, the sulfide solid electrolyte is Li2S-P2S5-LiCl, and the adhesive is PVDF.
[0094] The preparation method of the solid electrolyte membrane is the same as that of Example 1, wherein the particle size distribution of the first type sulfide electrolyte S1 is: Dmax (<2.0um), D50 (1.0-1.2um), the weight ratio of the polymer solid electrolyte P and the first type sulfide electrolyte S1 is 20:80, the first type composite solid electrolyte particles M11 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes on the surface, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10-50nm, and the particle size distribution of the first type composite solid electrolyte particles M11 is: Dmax (<2.5um), D50 (1.5-1.9um);
[0095] The particle size distribution of the second type sulfide electrolyte S2 is: Dmax (<1.0um), D50 (0.6-0.75um), the weight ratio of the polymer solid electrolyte P and the second type sulfide electrolyte S2 is 35:65, the second type composite solid electrolyte particles M21 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 40-80nm, and the particle size distribution of the second type composite solid electrolyte particles M21 is: Dmax (<1.7um), D50 (0.8-1.0um);
[0096] The thickness of the solid electrolyte prefabricated membrane F1 is 2-10 um, and the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is 60:30:10.
[0097] The all-solid electrolyte membrane and positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery, and this assembly is a conventional all-solid-state battery assembly method.
[0098] Different from the first embodiment, in the solid electrolyte membrane of the present embodiment, the adhesive used is PVDF.
[0099] Embodiment 7:
[0100] A solid electrolyte membrane for an all-solid-state battery, comprising a base membrane and a solid electrolyte prefabricated layer arranged on the surface of the base membrane, wherein the solid electrolyte prefabricated layer is arranged as a low-porosity structure with multi-dimensional particle size matching, the solid electrolyte prefabricated layer comprises a polymer solid electrolyte, a sulfide solid electrolyte and an adhesive, and the sulfide solid electrolyte is uniformly coated by the polymer solid electrolyte, the base membrane material is one of a polyimide membrane, a polyetherimide membrane, a polytetrafluoroethylene membrane, a cellulose membrane, a polyester membrane, and a polyacrylonitrile-based composite membrane, and the polymer solid electrolyte is a polyimide membrane. At least one or more of ethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, and hydrogenated nitrile rubber, wherein the sulfide solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one or more of.
[0101] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polyester membrane, the polymer solid electrolyte is PEO, the sulfide solid electrolyte is Li2S-P2S5-LiCl, and the adhesive is PTFE.
[0102] The preparation method of the solid electrolyte membrane is the same as that of Example 1, wherein the particle size distribution of the first type sulfide electrolyte S1 is: Dmax (<2.0um), D50 (1.0-1.2um), the weight ratio of the polymer solid electrolyte P and the first type sulfide electrolyte S1 is 20:80, the first type composite solid electrolyte particles M11 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes on the surface, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10-50nm, and the particle size distribution of the first type composite solid electrolyte particles M11 is: Dmax (<2.5um), D50 (1.5-1.9um);
[0103] The particle size distribution of the second type sulfide electrolyte S2 is: Dmax (<1.0um), D50 (0.6-0.75um), the weight ratio of the polymer solid electrolyte P and the second type sulfide electrolyte S2 is 35:65, the second type composite solid electrolyte particles M21 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 40-80nm, and the particle size distribution of the second type composite solid electrolyte particles M21 is: Dmax (<1.7um), D50 (0.8-1.0um);
[0104] The thickness of the solid electrolyte prefabricated membrane F1 is 2-10 um, and the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is 60:30:10.
[0105] The all-solid electrolyte membrane and positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery, and this assembly is a conventional all-solid-state battery assembly method.
[0106] Different from Example 1, in the solid electrolyte layer of the solid electrolyte membrane of this example, the base film is a polyester film.
[0107] Embodiment 8:
[0108] A solid electrolyte membrane for an all-solid-state battery, comprising a base membrane and a solid electrolyte prefabricated layer arranged on the surface of the base membrane, wherein the solid electrolyte prefabricated layer is arranged as a low-porosity structure with multi-dimensional particle size matching, the solid electrolyte prefabricated layer comprises a polymer solid electrolyte, a sulfide solid electrolyte and an adhesive, and the sulfide solid electrolyte is uniformly coated by the polymer solid electrolyte, the base membrane material is one of a polyimide membrane, a polyetherimide membrane, a polytetrafluoroethylene membrane, a cellulose membrane, a polyester membrane, and a polyacrylonitrile-based composite membrane, and the polymer solid electrolyte is a polyimide membrane. At least one or more of ethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, and hydrogenated nitrile rubber, wherein the sulfide solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one or more of.
[0109] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is PEO, the sulfide solid electrolyte is Li2S-P2S5-LiCl, and the adhesive is PTFE.
[0110] The preparation method of the solid electrolyte membrane is the same as that of Example 1, wherein the particle size distribution of the first type sulfide electrolyte S1 is: Dmax (<2.0um), D50 (1.0-1.2um), the weight ratio of the polymer solid electrolyte P and the first type sulfide electrolyte S1 is 30:70, the first type composite solid electrolyte particles M11 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes on the surface, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10-50nm, and the particle size distribution of the first type composite solid electrolyte particles M11 is: Dmax (<2.5um), D50 (1.5-1.9um);
[0111] The particle size distribution of the second type sulfide electrolyte S2 is: Dmax (<1.0um), D50 (0.6-0.75um), the weight ratio of the polymer solid electrolyte P and the second type sulfide electrolyte S2 is 35:65, the second type composite solid electrolyte particles M21 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 40-80nm, and the particle size distribution of the second type composite solid electrolyte particles M21 is: Dmax (<1.7um), D50 (0.8-1.0um);
[0112] The thickness of the solid electrolyte prefabricated membrane F1 is 2-10 um, and the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is 60:30:10.
[0113] The all-solid electrolyte membrane and positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery, and this assembly is a conventional all-solid-state battery assembly method.
[0114] Different from Example 1, in this embodiment, during the preparation of the first type of composite solid electrolyte particles M11, the weight ratio of the polymer solid electrolyte P to the first type of sulfide electrolyte S1 is 30:70.
[0115] Embodiment 9:
[0116] A solid electrolyte membrane for an all-solid-state battery, comprising a base membrane and a solid electrolyte prefabricated layer arranged on the surface of the base membrane, wherein the solid electrolyte prefabricated layer is arranged as a low-porosity structure with multi-dimensional particle size matching, the solid electrolyte prefabricated layer comprises a polymer solid electrolyte, a sulfide solid electrolyte and an adhesive, and the sulfide solid electrolyte is uniformly coated by the polymer solid electrolyte, the base membrane material is one of a polyimide membrane, a polyetherimide membrane, a polytetrafluoroethylene membrane, a cellulose membrane, a polyester membrane, and a polyacrylonitrile-based composite membrane, and the polymer solid electrolyte is a polyimide membrane. At least one or more of ethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, and hydrogenated nitrile rubber, wherein the sulfide solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one or more of.
[0117] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is PEO, the sulfide solid electrolyte is Li2S-P2S5-LiCl, and the adhesive is PTFE.
[0118] The preparation method of the solid electrolyte membrane is the same as that of Example 1, wherein the particle size distribution of the first type sulfide electrolyte S1 is: Dmax (<2.0um), D50 (1.0-1.2um), the weight ratio of the polymer solid electrolyte P and the first type sulfide electrolyte S1 is 20:80, the first type composite solid electrolyte particles M11 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes on the surface, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10-50nm, and the particle size distribution of the first type composite solid electrolyte particles M11 is: Dmax (<2.5um), D50 (1.5-1.9um);
[0119] The particle size distribution of the second type sulfide electrolyte S2 is: Dmax (<1.0um), D50 (0.6-0.75um), the weight ratio of the polymer solid electrolyte P and the second type sulfide electrolyte S2 is 40:60, the second type composite solid electrolyte particles M21 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 40-80nm, and the particle size distribution of the second type composite solid electrolyte particles M21 is: Dmax (<1.7um), D50 (0.8-1.0um);
[0120] The thickness of the solid electrolyte prefabricated membrane F1 is 2-10 um, and the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is 60:30:10.
[0121] The all-solid electrolyte membrane and positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery, and this assembly is a conventional all-solid-state battery assembly method.
[0122] Different from Example 1, in this embodiment, during the preparation of the second type of composite solid electrolyte particles M21, the weight ratio of the polymer solid electrolyte P to the first type of sulfide electrolyte S2 is 40:60.
[0123] Embodiment 10:
[0124] A solid electrolyte membrane for an all-solid-state battery, comprising a base membrane and a solid electrolyte prefabricated layer arranged on the surface of the base membrane, wherein the solid electrolyte prefabricated layer is arranged as a low-porosity structure with multi-dimensional particle size matching, the solid electrolyte prefabricated layer comprises a polymer solid electrolyte, a sulfide solid electrolyte and an adhesive, and the sulfide solid electrolyte is uniformly coated by the polymer solid electrolyte, the base membrane material is one of a polyimide membrane, a polyetherimide membrane, a polytetrafluoroethylene membrane, a cellulose membrane, a polyester membrane, and a polyacrylonitrile-based composite membrane, and the polymer solid electrolyte is a polyimide membrane. At least one or more of ethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, and hydrogenated nitrile rubber, wherein the sulfide solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one or more of.
[0125] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is PEO, the sulfide solid electrolyte is Li2S-P2S5-LiCl, and the adhesive is PTFE.
[0126] The preparation method of the solid electrolyte membrane is the same as that of Example 1, wherein the particle size distribution of the first type sulfide electrolyte S1 is: Dmax (<2.0um), D50 (1.0-1.2um), the weight ratio of the polymer solid electrolyte P and the first type sulfide electrolyte S1 is 20:80, the first type composite solid electrolyte particles M11 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes on the surface, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10-50nm, and the particle size distribution of the first type composite solid electrolyte particles M11 is: Dmax (<2.5um), D50 (1.5-1.9um);
[0127] The particle size distribution of the second type sulfide electrolyte S2 is: Dmax (<1.0um), D50 (0.6-0.75um), the weight ratio of the polymer solid electrolyte P and the second type sulfide electrolyte S2 is 35:65, the second type composite solid electrolyte particles M21 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 40-80nm, and the particle size distribution of the second type composite solid electrolyte particles M21 is: Dmax (<1.7um), D50 (0.8-1.0um);
[0128] The thickness of the solid electrolyte prefabricated film F1 is 2-10 um, and the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated film F1 is 55:30:15.
[0129] The all-solid electrolyte membrane and positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery, and this assembly is a conventional all-solid-state battery assembly method.
[0130] Different from Example 1, in this example, the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is 55:30:15.
[0131] Comparative Example 1
[0132] Different from Example 1, the solid electrolyte membrane of this comparative example is obtained by cooling the mixed slurry through a mold, and the specific preparation method is as follows:
[0133] The polymer solid electrolyte PEO, the sulfide solid electrolyte Li2S-P2S5-LiCl, the adhesive PTFE, and the solvent toluene are stirred and mixed in a weight ratio of 22.5:67.5:10:100 (wherein the first type sulfide electrolyte S1 and the second type sulfide electrolyte S2 are mixed and calculated, and the ratio is consistent with that in Example 1) to obtain a first slurry, which is applied onto a polytetrafluoroethylene membrane with a thickness of 10 μm, vacuum dried, and a solid electrolyte membrane is obtained according to the preparation method of Example 1.
[0134] The obtained solid electrolyte membrane is then combined with the purchased positive electrode sheet and negative electrode sheet to form a 2Ah all-solid-state battery. This assembly is a conventional all-solid-state battery assembly method. The rest is referred to Example 1.
[0135] Comparative Example 2
[0136] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is PEO, the sulfide solid electrolyte is Li2S-P2S5-LiCl, the adhesive is PTFE, and the weight ratio of the polymer solid electrolyte, the sulfide solid electrolyte, and the adhesive is 22.5:67.5:10 (wherein the first type sulfide electrolyte S1 and the second type sulfide electrolyte S2 are mixed and calculated, and the ratio is consistent with Example 1).
[0137] The preparation method of the solid electrolyte membrane is the same as that of Example 1. The all-solid electrolyte membrane and the positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery. This assembly is a conventional all-solid-state battery assembly method.
[0138] Different from Example 1, in the solid electrolyte layer of the solid electrolyte membrane of this embodiment, the ratio of the polymer solid electrolyte, the sulfide solid electrolyte and the adhesive is consistent with that in Example 1, and the electrolyte prefabricated membrane preparation method also remains consistent with that in Example 1, but there is no process of the first type of composite solid electrolyte particles M11 and the second type of composite solid electrolyte particles M21.
[0139] Comparative Example 3
[0140] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is PEO, the sulfide solid electrolyte is Li2S-P2S5-LiCl, and the adhesive is PTFE.
[0141] During the preparation of the first type of composite solid electrolyte particles M11, the weight ratio of the polymer solid electrolyte P and the first type of sulfide electrolyte S1 is 50:50.
[0142] The preparation method of the solid electrolyte membrane is the same as that of Example 1. The all-solid electrolyte membrane and the positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery. This assembly is a conventional all-solid-state battery assembly method.
[0143] Different from Example 1, in this embodiment, during the preparation of the first type of composite solid electrolyte particles M11, the weight ratio of the polymer solid electrolyte P to the first type of sulfide electrolyte S1 is 50:50.
[0144] Comparative Example 4
[0145] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is PEO, the sulfide solid electrolyte is Li2S-P2S5-LiCl, and the adhesive is PTFE.
[0146] During the preparation of the second type of composite solid electrolyte particles M21, the weight ratio of the polymer solid electrolyte P to the second type of sulfide electrolyte S2 is 50:50.
[0147] The preparation method of the solid electrolyte membrane is the same as that of Example 1. The all-solid electrolyte membrane and the positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery. This assembly is a conventional all-solid-state battery assembly method.
[0148] Different from Example 1, in this embodiment, during the preparation of the second type composite solid electrolyte particles M21, the weight ratio of the polymer solid electrolyte P to the second type sulfide electrolyte S2 is 50:50.
[0149] Comparative Example 5
[0150] In this embodiment, the electrolyte membrane in the all-solid-state battery adopts the above-mentioned solid electrolyte membrane, the base membrane is a polytetrafluoroethylene membrane, the polymer solid electrolyte is PEO, the sulfide solid electrolyte is Li2S-P2S5-LiCl, and the adhesive is PTFE.
[0151] The ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is 75:20:5.
[0152] The preparation method of the solid electrolyte membrane is the same as that of Example 1. The all-solid electrolyte membrane and the positive / negative electrode sheets obtained above are assembled into a 2Ah all-solid-state battery. This assembly is a conventional all-solid-state battery assembly method.
[0153] Different from Example 1, in this example, the ratio of M11, M21 and adhesive in the solid electrolyte prefabricated membrane F1 is 75:20:5.
[0154] Among them, the raw materials used in the manufacture of the all-solid-state electrolyte membrane do not contain organic solvents, so the baking process can be reduced during the production process, the production cost can be reduced, and the production efficiency can be improved. The base film is introduced into the all-solid-state electrolyte membrane to improve the strength of the membrane, so that the thickness of the all-solid-state electrolyte membrane can be made thinner. In the manufacturing process of the all-solid-state electrolyte membrane, the polymer solid electrolyte is first melted, and then the polymer solid electrolyte is fully mixed to coat the sulfide solid electrolyte, which can reduce the moisture sensitivity of the sulfide solid electrolyte. Because the polymer solid electrolyte is elastic, the sulfide solid electrolyte coated with the polymer solid electrolyte can make the electrolyte particles contact better during the charging and discharging process of the battery, and the compatibility of the electrolyte membrane with the positive / negative electrode sheets is also better, which improves the battery rate performance and cycle life. In addition, by matching different proportions of solid electrolyte particles with different particle size distributions, the solid electrolyte membrane obtained has lower pores, so as to achieve better ion transmission performance, reduce interface resistance, and improve the overall performance of the battery.
[0155] The all-solid electrolyte membranes and all-solid-state batteries obtained in the above-mentioned Examples 1 to 10 and Comparative Examples 1 to 5 were subjected to performance tests, including electrolyte membrane thickness, tensile strength; battery impedance, rate and cycle performance tests.
[0156] The test method for the tensile strength of the electrolyte membrane is:
[0157] Prepare a solid electrolyte membrane sample of 20mm*200mm size, use a tensile machine to stretch the sample until it breaks, record the tensile force as F, and the sample cross-sectional area as S. Calculate the tensile strength as: F / S.
[0158] The impedance test method is:
[0159] Adjust the battery SOC to 50% with 0.5C current, leave it for 2h, record the voltage U0, discharge it with 1.5C constant current for 30s, record the voltage U1; calculate DCR as: (U0-U1) / I (1.5C) .
[0160] The rate test method is:
[0161] Charge with 0.5C current to the upper cut-off voltage; leave for 30 min; discharge with 0.2C current to the lower cut-off voltage, record the capacity C0; leave for 30 min; charge with 0.5C current to the upper cut-off voltage; leave for 30 min; discharge with 1C current to the lower cut-off voltage, record the capacity C1; calculate the rate retention rate: (C1 / C0*100%).
[0162] The cycle performance test method is:
[0163] Charge with 0.5C current to the upper cut-off voltage; leave for 30 minutes; discharge with 0.5C current to the lower cut-off voltage; leave for 30 minutes; repeat the above steps for 200 cycles; record the capacity C1 of the first cycle and the capacity C of the 200th cycle 200 ; Calculate the cycle capacity retention rate: (C 200 / C1*100%).
[0164] The test results are shown in Table 1 below.
[0165]
[0166]
[0167] Table 1 Test data of each group of embodiments and comparative examples
[0168] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0169] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0170] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An all-solid electrolyte membrane, characterized in that: It comprises a base film and a solid electrolyte prefabricated layer arranged on the surface of the base film, wherein the solid electrolyte prefabricated layer is arranged as a low-porosity structure with multi-dimensional particle size matching; The solid electrolyte prefabricated layer comprises a polymer solid electrolyte, a sulfide solid electrolyte and an adhesive, and the sulfide solid electrolyte is uniformly coated by the polymer solid electrolyte.
2. The all-solid electrolyte membrane according to claim 1, characterized in that: The base film material is one of polyimide film, polyetherimide film, polytetrafluoroethylene film, cellulose film, polyester film and polyacrylonitrile-based composite film.
3. The all-solid electrolyte membrane according to claim 1, characterized in that: The thickness of the base film is 3-15 um, the porosity of the base film is 50%-90%, the tensile strength of the base film is 50-200 MPa, and the thickness of the solid electrolyte film is 5-15 um.
4. The all-solid electrolyte membrane according to claim 1, characterized in that: The polymer solid electrolyte is at least one or more of polyethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene copolymer, and hydrogenated nitrile rubber.
5. The all-solid electrolyte membrane according to claim 1, characterized in that: The sulfide solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one or more of.
6. A method for preparing an all-solid electrolyte membrane, characterized in that: The following steps are involved: The first step is to prepare the first type of composite solid electrolyte particles M11; Add a polymer solid electrolyte P into a high-temperature vacuum mixer, fully melt it under certain temperature and stirring conditions, add a first-type sulfide electrolyte S1, fully mix it under certain temperature and stirring conditions to form a molten slurry M10, and use a spray device to spray M10 into first-type composite solid electrolyte particles M11; The second step is to prepare the second type of composite solid electrolyte particles M21: Add a polymer solid electrolyte P into a high-temperature vacuum mixer, fully melt it under certain temperature and stirring conditions, add a second type of sulfide electrolyte S2, fully mix it under certain temperature and stirring conditions to form a molten slurry M20, and use a spray device to spray M20 into first type composite solid electrolyte particles M21; The third step is the preparation of the solid electrolyte prefabricated membrane F1: M11, M21 and a binder are mixed evenly according to a certain ratio, and then the binder is fiberized and granulated so that the binder fibers fully contact and cover the M11 and M21 particles, and the M11 and M21 particles covered with the binder fibers are pressed into a solid electrolyte prefabricated membrane F1 by a membrane forming device; The fourth step is the preparation of all-solid electrolyte membrane FF: The base film F0 and the solid electrolyte prefabricated film F1 are pressed into a solid electrolyte membrane FF under certain temperature and pressure conditions using a hot pressing device.
7. The method for preparing an all-solid electrolyte membrane according to claim 6, characterized in that: The stirring temperature in the first step is 50-200°C, the particle size distribution of the first type sulfide electrolyte S1 is Dmax (<2.0um), D50 (1.0~1.2um), the weight ratio of the polymer solid electrolyte P and the first type sulfide electrolyte S1 is (15:85)~(35:65), the first type of composite solid electrolyte particles M11 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes on the surface, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 10~50nm, and the particle size distribution of the first type of composite solid electrolyte particles M11 is Dmax (<2.5um), D50 (1.5~1.9um).
8. The method for preparing an all-solid electrolyte membrane according to claim 6, characterized in that: In the first step, the particle size distribution of the second type sulfide electrolyte S2 is Dmax (<1.0um), D50 (0.6~0.75um), the weight ratio of the polymer solid electrolyte P and the second type sulfide electrolyte S2 is (30:70)~(45:55), the second type of composite solid electrolyte particles M21 are polymer solid electrolyte particles or sulfide solid electrolytes coated with polymer solid electrolytes on the surface, wherein the thickness of the polymer solid electrolyte coated on the surface of the sulfide solid electrolyte is 40~80nm, and the particle size distribution of the second type of composite solid electrolyte particles M21 is: Dmax (<1.7um), D50 (0.8~1.0um).
9. The method for preparing an all-solid electrolyte membrane according to claim 6, characterized in that: In the third step, the adhesive comprises one of PVDF and PTFE, and the thickness of the solid electrolyte prefabricated membrane F1 is 2 to 10 um. The ratio of M11, M21 and the adhesive in the solid electrolyte prefabricated membrane F1 is (65:25:10) to (50:35:15).
10. The method for preparing an all-solid electrolyte membrane according to claim 6, characterized in that: The temperature of the fourth step is 45° C. to 90° C., and the pressure is 5 to 20 MPa.